Insulin-like Growth Factor-1 as a possible alternative to Bone Morphogenetic Protein-7 to induce osteogenic differentiation of human mesenchymal stem cells in vitro - Reible, Bruno; Schmidmaier, Gerhard; Moghaddam-Alvandi, Arash; Westhauser, Fabian (International journal of molecular sciences, 2018)
Growth factors and mesenchymal stem cells (MSC) support consolidation of bone defects. Bone Morphogenetic Protein-7 (BMP-7) has been used clinically and experimentally, but the outcomes remain controversial. Increased systemic expression of Insulin-like Growth Factor-1 (IGF-1) significantly correlates with successful regeneration of bone healing disorders, making IGF-1 a promising alternative to BMP-7. There is no experimental data comparing the osteoinductive potential of IGF-1 and BMP-7. Therefore, in this study, the influence of IGF-1 and BMP-7 in different concentrations on the osteogenic differentiation of two human MSC-subtypes, isolated from reaming debris (RMSC) and iliac crest bone marrow (BMSC) has been assessed. A more sensitive reaction of BMSC towards stimulation with IGF-1 in concentrations of 400–800 ng/mL was found, leading to a significantly higher degree of osteogenic differentiation compared to stimulation with BMP-7. RMSC react more sensitively to stimulation with BMP-7 compared to BMSC. Lower concentrations of IGF-1 were necessary to significantly increase osteogenic differentiation of RMSC and BMSC compared to BMP-7. Therefore, IGF-1 should be considered as a valuable option to improve osteogenic differentiation of MSC and merits further experimental consideration. The MSC subtype and method of differentiation factor application also have to be considered, as they affect the outcome of osteogenic differentiation.